Advances in sewage treatment proceedings of the conference held on 14 November 1972 at the Institution of Civil Engineers. (Thomas Telford, 1973)
Topics of papers at the conference include: preliminary treatment and sedimentation; Secondary treatment; advanced treatment; and sludge disposal.